A Rapid, Stability Indicating RP-UPLC Method for Determination of Paliperidone Palmitate in a Depot Injectable Formulation - Rakshit Kanubhai Trivedi & , Prashant Jain, Mukesh C Patel, Parimal M Chatrabhuji, Dipika R Trivedi (Journal of Applied Pharmaceutical Science, 2013)
A rapid, stability-indicating reversed phase ultra-performance liquid chromatographic (RP-UPLC) method was developed for the determination of paliperidone palmitate (PP), in depot injectable dosage form. The chromatographic separation was achieved on an Acquity BEH C18 (50 mm × 2.1 mm, 1.7 µm) column, with a mobile phase consisting of ammonium acetate buffer, and acetonitrile at a ratio of 10:90 (v/v) and a flow rate of 0.6 mL/min. The eluted compound was monitored at a wavelength of 238 nm using a UV detector. The method described herein separated paliperidone palmitate from all other formulation components and two major known degradation products (N-Oxide and paliperidone) within a run time of 2.5 min. The method also generated linear results over a PP concentration range of 156 to 468 µg/mL. The stability indicating capability of the method was established by performing forced degradation experiments. The RP-UPLC method that was developed was validated according to the International Conference on Harmonization (ICH) guidelines. This method was successfully applied in the quantitative determination of PP in a stability study of paliperidone palmitate depot injection. The procedure described herein is simple, selective, and reliable for routine quality control analysis as well as stability testing.
Keywords: Depot , Chromatography, Extended-release suspension,